Evaluation of Intravitreal Ranibizumab on the Surgical Outcome for Diabetic Retinopathy With Tractional Retinal Detachment. Issue 8 (February 2016) - Dong, Feng; Yu, Chenying; Ding, Haiyuan; Shen, Liping; Lou, Dinghua
Abstract : Abstract: This study aims to investigate intravitreal injection of Ranibizumab on the surgical outcome for diabetic patients who had tractional retinal detachment but did not receive any preoperative retinal photocoagulation. Ninety-seven patients (97 eyes) who had diabetic retinopathy with tractional retinal detachment were enrolled to receive 23-G pars plana vitrectomy (PPV). They were assigned to an experimental group (Group I, n = 47 eyes) and a control group (Group II, n = 50 eyes). The patients in Group I were given 1 injection of intravitreal Ranibizumab (Lucentis 0.5 mg/0.05 mL) 1 week before surgery, whereas those in Group II went down to surgery directly. Follow-ups were performed for 6 months to 3 years (16 ± 6 months), and indicators observed included postoperative best-corrected visual acuity, complications, and retinal thickness in the macula measured by optical coherence tomography. In Group I, BCVA improved from logMAR 1.92 ± 0.49 to logMAR 0.81 ± 0.39 following surgery, whereas in Group II, BCVA improved from logMAR 1.91 ± 0.49 to logMAR 0.85 ± 0.41. There was significant postoperative gain in vision, but there was no significant difference between the 2 groups at postoperative follow-up visits. The mean duration of vitrectomy in Group I and Group II was (40 ± 7) minutes and (53 ± 9) minutes, respectively, with significant difference. Iatrogenic breaks were noted in 5 eyes (11%) in the experimental group and 17 eyes (34%) in the control group; the difference was significant. The retinal thickness in the macula measured by OCT was (256 ± 44) μm and (299 ± 84) μm in Group I and Group II respectively with significant difference. Besides, there were significantly more eyes in Group II that required silicone oil tamponade and postoperative retinal photocoagulation. 23-G PPV combined with intravitreal tamponade and panretinal photocoagulation still remains an effective regimen for the treatment of diabetic retinopathy complicated with tractional retinal detachment. Preoperative intravitreal injection of Ranibizumab could shorten surgical duration, reduce intraoperative complications, and sometimes spare the need for silicone oil tamponade and postoperative retinal photocoagulation, alleviating patients' suffering from surgery.